The Poetics of the Novella in Correlation to Vasyl Stefanyk's Artistic Vision - Khorob, Stepan (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article discusses correlations between artistic vision and poetics in Vasyl Stefanyk’s novellas. It is argued that the writer’s modernist aesthetic experience left its imprint on his literary works. The author concludes that the writer’s artistic vision followed a dynamic course of development correlating with the poetics of the novella and enriching the stylistic color scheme of his narrative prose.